PERCEIVED ORGANIZATIONAL SUPPORT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR: THE MEDIATING ROLE OF PSYCHOLOGICAL CAPITAL - Mohamed Azim, Abdul Mutalib; Dora, Mohd Taib (Journal of Human Capital Development (JHCD), 2016)
The present study was conducted to identify the mediating role of psychological capital in the relationship between Perceived Organizational Support (POS) and Organizational Citizenship Behavior (OCB) among employees of multimedia organizations in Malaysia. Data collection was done through personally administered questionnaires from 350 employees. The statistical analysis namely Correlation analysis, Confirmatory Factor Analysis and Structural Equation Modelling were executed. Results found positive and significant relationship between POS and OCB, a positive relationship between POS and psychological capital, and psychological capital towards OCB. Finally, psychological capital fully mediated the relationship between POS and OCB. The study makes a significant and unique contribution to literature by showing the mediation effect of psychological capital in the relationship between POS and OCB. Present study’s results demonstrated that the employees’ perception of organization support, can enhance employee’s psychological capital which in turn effect OCB. Keywords: psychological capital, perceived organizational support, organizational citizenship behavior